Answer:
A. ![7\frac{34}{24}](https://tex.z-dn.net/?f=7%5Cfrac%7B34%7D%7B24%7D)
Step-by-step explanation:
We are given the expression, ![8\frac{10}{24}](https://tex.z-dn.net/?f=8%5Cfrac%7B10%7D%7B24%7D)
On re-writing the expression after borrowing 1, we have,
=
i.e.
= ![7(\frac{10}{24}+\frac{24}{24})](https://tex.z-dn.net/?f=7%28%5Cfrac%7B10%7D%7B24%7D%2B%5Cfrac%7B24%7D%7B24%7D%29)
i.e.
= ![7\frac{34}{24}](https://tex.z-dn.net/?f=7%5Cfrac%7B34%7D%7B24%7D)
Thus, the equivalent expression after borrowing 1 from the given expression is
.
Hence, option A is correct.
Answer:
x is 3
Step-by-step explanation:
6 (x + 1) = 24
6 (x) + 6(1) = 24
6x + 6 = 24
Subtract 6 on both sides
6x + 6 - 6 = 24 - 6
6x + 0 = 18
6x = 18
x = 18/6
x = 3
A
i need to put 20 characters in here so imma tell you, just use desmos.com. if you type in the equations, it’ll show you the graph
Answer:
12
Step-by-step explanation: